How Do Older Adults Experience Depression and Social Isolation in Nursing Homes? A Descriptive Phenomenological Study - Azizah, Lilik Ma’rifatul; Akbar, Amar; Zainuri, Imam; Khotijah, Siti (Chakra Brahmanda Lentera Institute, 2026)
Background: Depression and social isolation are common psychosocial problems among older adults living in nursing homes. Institutional living may intensify feelings of loneliness, loss of meaningful roles, and emotional withdrawal, which can negatively affect psychological well-being and quality of life. Understanding the lived experiences of older adults is essential to inform holistic nursing care. This study aimed to explore the lived experiences of depression and social isolation among older adults residing in nursing homes. Methods: A qualitative study using a descriptive-phenomenological approach and following COREQ guidelines was conducted. Using purposive sampling, 15 potential participants were approached; 12 participants met the inclusion criteria (aged ≥60, residing ≥3 months, and GDS score ≥5) and completed the study, while 3 declined due to health fatigue. Data were collected through in-depth, face-to-face interviews and analyzed using the Colaizzi method to identify essential themes. Ethical approval was obtained before data collection, and data collection continued until data saturation was achieved at the 12th participant. Results: Six major themes emerged: Feeling forgotten and abandoned; Living among others yet feeling alone; Loss of role and identity; Emotional withdrawal and silence; Longing for meaningful connection; and Searching for acceptance and inner peace. Conclusion: Depression and social isolation are deeply rooted in perceived loss and unmet emotional needs. Practical implications include the need for psychosocial nursing interventions that prioritize meaningful interpersonal communication and family engagement strategies.